Substituting x=1.6 into the equation 6-4x=-x/4 doesn't result in an equality, hence, x=1.6 doesn't satisfy this equation.
To verify if x=1.6 satisfies the equation 6-4x=-x/4, we just need to substitute 1.6 in the place of x in the equation and check if both sides of the equation balance. The left side of the equation would then be: 6-4(1.6) = 0.4. The right side of the equation becomes: -1.6/4 = -0.4. As we can see the left side of the equation doesn't equal the right side, hence, x=1.6 doesn't satisfy the equation 6-4x=-x/4.
#SPJ2
(-y2 – 4y - 8) – (-4y2 – 6y + 3)
Answer:
3y^2 +2y -11
Step-by-step explanation:
(-y^2 – 4y - 8) – (-4y^2 – 6y + 3)
Distribute the minus sign
(-y^2 – 4y - 8) +4y^2 + 6y - 3
Combine like terms
-y^2+4y^2 – 4y + 6y - 3-8
3y^2 +2y -11
Answer:
3y^2+2y-11
Step-by-step explanation:
I am guessing for -y2 and -4y2 you meant exponents; it would still get you the same answer though.
-y^2-4y-8 - (-4y2-6y+3)
1.Distribute; -y^2-4y-8 -1(-4y2*-1-6y*-1+3*-1)
you then get; -y^2+(-4y)+(-8) +4y^2+6y+-3
2.Combine like terms; 3y^2+2y-11
Then you get: 3y^2+2y-11.
Answer:
if youre simplifying, then the answer is -3y+46
Step-by-step explanation:
4(3-5y)+17(y+2)
12-20y+17y+34
-3y+46
Slope Form
Distance Formula
Quadratic Formula